Agriculture in Himachal Pradesh and Its Neighbouring Himalayan States: The Present Scenario (Indian Journal of Hill Farming, 2022)
Agriculture in the mountainous states of North-Western India is a very difficult activity as it faces climate adversities like severe winters, snowfall, heavy rainfall, landslides etc. throughout the year. These problems have made livelihood of people in these states difficult, however most of the farmers in these states are solely dependent on their agriculture for livelihood. Therefore the present paper is an attempt to understand the situation of agriculture in the three Himalayan states of India i.e. Himachal Pradesh, Jammu-Kashmir and Uttarakhand. To understand the situation of agriculture in these states change in the area and production of various crops has been analyzed for the years 2001 and 2015. The results of the study have highlighted that the area under almost every crop in these states has decreased, however improved agricultural infrastructure and availability of other facilities in agriculture has led to an increase in its production.